2006
DOI: 10.1167/iovs.06-0018
|View full text |Cite
|
Sign up to set email alerts
|

Serial Measurements of Higher-Order Aberrations after Blinking in Normal Subjects

Abstract: Dynamic changes in HOAs after blinking showed variations even in clinically normal subjects. Serial measurements of HOAs may be useful in evaluating the dynamic changes in tear film and the effects on the quality of vision after blinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 36 publications
6
82
0
Order By: Relevance
“…Several studies have investigated the influence of tear film dynamics on sequential wavefront aberrations in dry eyes and normal eyes. 26,31,32 Nowadays, wavefront sensing has been recognized as a practical objective method for evaluating sequential changes in optical quality of the eye. Thus, in the present study, we examined the sequential changes in ocular aberrations with the wavefront aberrometer to comprehend the detailed influence of eye ointment on ocular optical quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated the influence of tear film dynamics on sequential wavefront aberrations in dry eyes and normal eyes. 26,31,32 Nowadays, wavefront sensing has been recognized as a practical objective method for evaluating sequential changes in optical quality of the eye. Thus, in the present study, we examined the sequential changes in ocular aberrations with the wavefront aberrometer to comprehend the detailed influence of eye ointment on ocular optical quality.…”
Section: Discussionmentioning
confidence: 99%
“…This system has been described in detail elsewhere. 26 Ten serial images were obtained at 1-sec intervals from 1 to 10 s following a blink. The subjects were instructed to keep their eyelids open during the image capture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, much attention has been paid to the effect of tear film on the optical quality of the eye, and several studies have indicated that tear film break-up degrades optical quality and fluctuations in the tear film causes increased irregular astigmatism [5, 8, 31, 32]. The greater rate of evaporation at the center of palpebral aperture causes the tear film to thin more rapidly at the center than at the periphery [31].…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of a smooth, intact tear film is essential for achieving high-quality retinal images [3, 4]. Several clinical studies support the hypothesis that increased aberration as a result of a tear film disruption may reduce retinal image quality [5,6,7,8,9,10]. This fact is supported by the finding that instillation of artificial tears in dry eyes reduces the optical aberrations and increases the optical quality of the retinal images [11,12,13].…”
Section: Introductionmentioning
confidence: 99%